Evaluación de las pérdidas de arroz en la mini cosechadora LOVOL AF-100 (Serie 0) en la Granja Agrícola Arrocera “Bartolomé Masó Márquez” - Benjamín Gabriel Gaskins Espinosa; Idalberto Macías Socarrás; Ernesto Reyna Pompa; Miguel Bolívar Zamorano Reyes; Antonio Luis Barrera Amat (European Scientific Journal, ESJ, 2018)
The investigation, refers to the Agricultural Farm of Rice "Bartolome Maso Marquez", located in the municipality of Yara, province of Granma, is dedicated to the production of rice, the objective is based on the total losses of the grains and the system of the machine, The quality of the harvested product is also evaluated, using the LOVOL-AF 100 (Series 0) mini harvester. The combined losses were 5.98%; I found above the parameters set by the manufacturer of 5%; There are significant differences between the losses in the different parts of the combination, with a better performance in the 1.62% sieve, followed by agitation with 2.03%, in the pre-harvest the losses were 3.5% much higher than those established, of 1 %. ; The content of impurities in the harvested mass reached 13%, higher than the established in 30%, the concept of losses of the combine in total reached 23 920 t of clean rice, which represents the consumption of rice of 322 222 people in one year.